Increasing The Production of Thai Eggplant (Solanum melongena L.) Grown at Altitude of 2 Masl Using Mycorrhizal Biofertilizer - Rahman Hairuddin; S. Sachril (Universitas Sembilanbelas November Kolaka, 2019)
This study was aimed to increase the production of Thai eggplant (Solanum melongena L) grown at altitude of 2 masl using myccohirzal biofertilizer. The study was conducted in Experimental Farm of Agricultural Faculty of Campus II University of Cokroaminoto Palopo, Batu Pasi Sub-district, Wara Utara District, Palopo City. This research applied the method of Randomized Block Design with four replicants and five treatments; P0 = Without treatment (control), P1 = Mycorrhizal fertilizer of 5 gr/plant, P2 = Mycorrhizal fertilizer of 10 gr/plant, P3 = Mycorrhizal fertilizer of 15 gr/plant, and P4 = Mycorrhizal fertilizer of 20 gr/plant. Research of this study showed that one treatment significantly affected the root length of eggplant, namely P2 with root length of 39.42 cm. In general, application of mycorrhizal fertilizer did not significantly affect the growth and production of eggplant, but several doses resulted in better outcome. Treatment of P3 obtained the best plant height of 9.22 cm, while the best average flowering age was found in P2 and P4 of 31.8 days after planting. Moreover, P3 and P4 produced the most number of flower, namely 3.83 flowers, while the most number of fruits was obtained by P4 of 3.53 fruits. At last, P3 produced the heaviest fresh weight of fruit of 221.13 gram